Anti-mosquito microcapsule as well as preparation method and application thereof
By constructing an organic-inorganic synergistically reinforced shell and a multi-layered structure, the problem of easy breakage of mosquito repellent microcapsule shells was solved, and the compressive and impact resistance was improved, ensuring the stability and wear resistance of the mosquito repellent effect.
Patent Information
- Application Number
- CN202511634285.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-10
- Publication Date
- 2026-01-23
AI Technical Summary
The shell of existing mosquito-repellent microcapsules has insufficient mechanical strength and is prone to rupture under external forces, leading to leakage of the core material and affecting the mosquito-repellent effect and user experience.
By constructing an organic-inorganic synergistic reinforced shell material, chemical bonds are formed by the composite modification of nano-hydroxyapatite and dopamine, and a multi-layer structure is formed by combining polydopamine-polyurea flexible segments and aminated nano-silica, which enhances the compressive and impact resistance of the shell material. Furthermore, the surface charge of the shell material is homogenized by pretreatment with sodium dodecylbenzenesulfonate to ensure uniform assembly of the protective layer.
It significantly improves the compressive and impact resistance of microcapsules, prevents rupture, enhances the stability and abrasion resistance of mosquito repellent effect, and ensures integrity during use.
Smart Images

Figure CN121369372A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of mosquito-repelling microcapsules, in particular to a mosquito-repelling microcapsule, a preparation method and application thereof. BACKGROUND
[0002] As a high-efficiency mosquito-repelling component carrier, the mosquito-repelling microcapsule can effectively reduce the volatilization loss of the core material and improve the use safety by wrapping the mosquito-repelling core material in a high polymer shell material, and has been widely applied in the fields of mosquito-repelling fabrics, mosquito-repelling coatings and personal care products.
[0003] However, the practical application of the existing mosquito-repelling microcapsule still faces a core technical bottleneck, i.e., the mechanical strength of the shell material is insufficient and is prone to rupture under external action. The mosquito-repelling microcapsule applied to clothing fabrics is prone to damage of the shell material under the mechanical stirring and rubbing external force in daily washing, resulting in premature leakage and loss of the internal mosquito-repelling core material. This not only makes the mosquito-repelling components unable to be released slowly as expected, significantly shortening the product mosquito-repelling time, but also may cause local irritation to increase due to the concentrated leakage of the core material, reducing the use experience. Therefore, it is crucial to develop a mosquito-repelling microcapsule preparation method capable of improving the mechanical properties of the shell material and resisting external damage to solve the problem of core material leakage and ensure the mosquito-repelling effect. SUMMARY
[0004] The present application aims to provide a mosquito-repelling microcapsule, a preparation method and application thereof to solve the technical problem of insufficient mechanical strength of the shell material of the mosquito-repelling microcapsule proposed in the background. The mosquito-repelling microcapsule prepared by the present application has excellent mechanical strength, which can effectively prevent the shell material from being damaged under external force.
[0005] To achieve the above-mentioned purpose, the present application provides the following technical solutions:
[0006] A preparation method of a mosquito-repelling microcapsule, comprising the following steps:
[0007] S1, mixing citronella oil, lemon grass oil and peppermint oil to obtain a core material, dissolving sodium lignosulfonate and Tween-80 in deionized water, adjusting the pH, adding the core material, and then performing homogenization and ultrasonic treatment to obtain a core material emulsion;
[0008] S2, dispersing nano-hydroxyapatite in a mixed solution of ethanol and water, reacting the nano-hydroxyapatite with aminopropyl triethoxysilane to obtain silane-modified nano-hydroxyapatite, and then reacting the silane-modified nano-hydroxyapatite with dopamine hydrochloride in the presence of oxygen to obtain silane-dopamine complex-modified nano-hydroxyapatite;
[0009] S3, mixing the core material emulsion with the silane-dopamine complex-modified nano-hydroxyapatite, adding diisocyanate for reaction, then adding dopamine aqueous solution and passing oxygen for continuous reaction, and then performing centrifugation and washing to obtain a nano-composite microcapsule;
[0010] S4, dispersing the nanometer silicon dioxide in a mixed solution of ethanol and water, reacting it with aminopropyl triethoxysilane, centrifuging, washing and drying to obtain aminated nanometer silicon dioxide;
[0011] S5, sequentially performing multi-layer assembly of the nanocomposite microcapsule with polyallylamine hydrochloride, polyacrylic acid and aminated nanometer silicon dioxide, and repeating the process for multiple times, and drying to obtain the mosquito-repelling microcapsule.
[0012] In the technical scheme of the present application, the mechanical strength of the mosquito-repelling microcapsule is improved from two aspects. On the one hand, the mechanical properties are improved from the root by constructing an organic-inorganic synergistically enhanced shell material body to avoid rupture. Specifically, the nanometer hydroxyapatite is first modified by aminopropyl triethoxysilane and dopamine, which not only retains its inorganic rigidity (can disperse and extrude external forces such as stress transmission and tension to resist shell deformation), but also forms chemical bonding with polydopamine-polyurea through surface functional groups (avoids peeling of the reinforcing phase and the organic phase); the flexible segment of polydopamine-polyurea can alleviate the brittleness of pure inorganic materials, absorb impact energy and prevent the shell from being directly broken by external force, thereby significantly improving the compressive strength and impact resistance of the shell material, effectively resisting external forces during preparation or application (such as emulsion stirring and fabric padding), and reducing the risk of body rupture. On the other hand, a wear-resistant-impact-resistant protection system is constructed on the surface of the shell material to assist in avoiding rupture: aminated nanometer silicon dioxide as a wear-resistant particle forms a physical barrier to directly resist the frictional damage of the microcapsule and the external carrier (such as fabric fibers), reducing the rupture caused by surface scratches; the polyelectrolyte polyallylamine hydrochloride and polyacrylic acid form a dense multi-layer structure through electrostatic interaction, which can disperse local impact stress (such as external force during washing and rubbing), avoiding surface damage caused by stress concentration; at the same time, the multi-layer structure can block the erosion of the external environment (such as washing liquid and matrix components) on the shell material body, maintaining the mechanical stability of the body. Through the above two aspects, a synergistic effect of internal strength and external protection is formed, thereby avoiding the rupture of the microcapsule under external force.
[0013] Preferably, in step S1, the mass ratio of citronella oil, lemon grass oil and peppermint oil is 1:1 to 3:2 to 5.
[0014] Preferably, in step S2, the mass ratio of nanometer hydroxyapatite to aminopropyl triethoxysilane is 10:0.5 to 1.0.
[0015] Preferably, in step S3, the addition amount of silane-dopamine modified nanometer hydroxyapatite is 2 to 4 wt% of the mass of the core material emulsion.
[0016] Preferably, in step S3, the addition amount of diisocyanate is 8 to 12 wt% of the mass of the core material emulsion.
[0017] Preferably, in step S4, the mass ratio of the nanosilica to the aminopropyl triethoxysilane is 10:1-2.
[0018] Preferably, in step S5, the nanocomposite microcapsule is pretreated, including the following steps:
[0019] The nanocomposite microcapsule is added to deionized water, ultrasonic oscillation is performed to uniformly disperse, sodium dodecyl benzene sulfonate is added, stirring reaction is performed, and centrifugal separation, washing and drying are performed to obtain the pretreated nanocomposite microcapsule.
[0020] In the technical solution of the present application, the above-mentioned nanocomposite microcapsule is sequentially subjected to multilayer assembly with polyallylamine hydrochloride, polyacrylic acid and aminated nanosilica, but in the assembly process, the present application team found that the amino groups of the polyurea segment on the microcapsule shell material would be partially protonated to form weak positive electricity, and the weak positive electricity and the negative charge generated by the ionization of the polydopamine molecule would easily form local intrinsic electrostatic neutralization, resulting in serious disorder of the surface charge distribution of the composite shell material, and the appearance of uneven state of negative electricity enrichment area, electric neutral area and weak positive electricity area. This charge disorder directly causes uneven adsorption of the subsequent cationic polyelectrolyte polyallylamine hydrochloride, and the polyallylamine hydrochloride is only accumulated in a large amount in the area with high negative density, while the adsorption amount of polyallylamine hydrochloride in the electric neutral or weak positive electricity area is significantly insufficient, thereby causing the assembly of the subsequent aminated nanosilica and anionic polyelectrolyte polyacrylic acid to appear a layer due to the uneven distribution of polyallylamine hydrochloride, and the multilayer protective layer formed finally has obvious defects of local exposure and thickness difference, and cannot form uniform and effective protection on the surface of the microcapsule.
[0021] To further solve this technical problem, the nanocomposite microcapsule is pretreated, and sodium dodecyl benzene sulfonate is preferentially adsorbed on the surface of the polyurea segment through hydrophobic interaction. The anionic sulfonic acid group in the molecular structure of the sodium dodecyl benzene sulfonate can accurately neutralize the weak positive electricity generated by the protonation of the polyurea amino group, and at the same time form a charge synergistic effect with the negative group of the polydopamine molecule, so as to realize the homogenization regulation of the negative density on the surface of the composite shell material. The uniformized negative surface provides a stable and uniform electrostatic adsorption substrate for the cationic polyelectrolyte polyallylamine hydrochloride, ensures that the polyallylamine hydrochloride can uniformly cover the whole surface of the microcapsule, avoids the occurrence of assembly layer in the subsequent process, effectively solves the defects of local exposure and uneven thickness of the multilayer protective layer, and guarantees the uniform protection function of the microcapsule surface. Figure 1 and Figure 2 The SEM images of the surfaces of the microcapsules prepared in Example 1 and Comparative Example 3 are shown in FIGS. 1 and 2, respectively. It can be seen from the comparison that the surface of the microcapsule of Comparative Example 3 is obviously observed to have multiple pit structures, while the surface of the microcapsule prepared in Example 1 is smooth and smooth.
[0022] As preferred, the sodium dodecyl benzene sulfonate is added in an amount of 2-6% of the nanocomposite microcapsule.
[0023] An anti-mosquito microcapsule prepared by the method described above.
[0024] Use of an anti-mosquito microcapsule in fabric finishing agents.
[0025] Compared with the prior art, the present application has the following advantages:
[0026] (1) By constructing a polydopamine-polyurea-nano-hydroxyapatite organic-inorganic composite shell material, the rigidity of the inorganic phase is used to resist deformation, and the flexibility of the organic phase is used to alleviate brittleness, so that the anti-pressure and anti-impact strength of the microcapsule is fundamentally improved.
[0027] (2) By alternately assembling polyelectrolyte and amino-nano-silicon dioxide on the surface of the microcapsule, a dense multi-layer structure is formed. This structure not only disperses external impact stress, but also directly improves the wear resistance of the microcapsule by the rigid nanoparticles on its surface, achieving the effect of external protection.
[0028] (3) By using sodium dodecyl benzene sulfonate to pretreat the microcapsule, the surface charge of the shell material is uniformized, solving the problem of uneven assembly of the subsequent protective layer and local exposure caused by charge disorder, and ensuring the integrity and effectiveness of the surface protective layer function. BRIEF DESCRIPTION OF DRAWINGS
[0029] Figure 1 SEM image of the anti-mosquito microcapsule prepared in Example 1 of the present application.
[0030] Figure 2 SEM image of the anti-mosquito microcapsule prepared in Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor are within the scope of protection of the present application.
[0032] Example 1
[0033] A preparation method of an anti-mosquito microcapsule, comprising the following steps:
[0034] Step 1: 1 g of citronella oil, 2.5 g of lemongrass oil, and 4 g of peppermint oil were mixed to obtain a core material; 0.6 g of sodium lignosulfonate and 0.4 g of Tween-80 were dissolved in 100 mL of deionized water, and ultrasonic treatment was performed at 300 W for 15 min until dissolution; 0.1 mol / L NaOH was used to adjust the pH to 8.0, and then the core material was added; homogenization was performed at 8000 rpm for 5 min, and then ultrasonic treatment was performed at 400 W for 12 min to obtain a core material emulsion.
[0035] Step 2: 1.0 g of nano-hydroxyapatite was dispersed in 50 mL of an ethanol-water mixture (volume ratio of 3:1) and ultrasonic treatment was performed at 500 W for 30 min; the pH was adjusted to 5.5, 0.09 g of aminopropyltriethoxysilane was added, and reaction was performed at 65°C under nitrogen protection and stirring at 200 rpm for 5 h; centrifugal washing and drying were performed to obtain silane-modified nano-hydroxyapatite; the silane-modified nano-hydroxyapatite was dispersed in 50 mL of Tris-HCl buffer at pH=8.2, 0.043 g of dopamine hydrochloride was added, and reaction was performed at 28°C under stirring at 200 rpm and oxygen flow of 20 mL / min for 10 h; centrifugal washing and drying were performed to obtain silane-dopamine complex-modified nano-hydroxyapatite.
[0036] Step 3: 106 g of the core material emulsion was taken, 3.5 g of the silane-dopamine complex-modified nano-hydroxyapatite was added, ultrasonic treatment was performed at 300 W for 10 min, 11 g of diisocyanate was added dropwise, and reaction was performed at 30°C under stirring at 250 rpm for 1.5 h; 12 mL of an aqueous solution containing 0.3 g of dopamine hydrochloride was added, oxygen flow (20 mL / min) was introduced, and reaction was performed at 40°C under stirring at 250 rpm for 8 h; centrifugal separation was performed at 8000 rpm for 8 min, and water washing was performed three times to obtain nano-composite microcapsules.
[0037] Step 4: 0.5 g of nano-silicon dioxide was dispersed in 50 mL of an ethanol-water mixture (volume ratio of 4:1), ultrasonic treatment was performed at 400 W for 25 min, the pH was adjusted to 5.5, 0.09 g of aminopropyltriethoxysilane was added, and reaction was performed at 85°C under reflux and stirring at 180 rpm for 9 h under nitrogen protection; centrifugal separation was performed at 8000 rpm for 12 min, anhydrous ethanol washing was performed three times, water washing was performed twice, and vacuum drying was performed at 70°C for 5 h to obtain aminated nano-silicon dioxide.
[0038] Step 5: 1.0 g of the nano-composite microcapsules was taken, 100 mL of deionized water was added, and ultrasonic treatment was performed at 200 W for 5 min until dispersion; 0.05 g of sodium dodecylbenzenesulfonate was added, and stirring was performed at 25°C and 150 rpm for 30 min; centrifugal separation was performed at 4000 rpm for 10 min, deionized water washing was performed three times, and drying was performed at 50°C to obtain pretreated microcapsules.
[0039] The pretreated microcapsules were dispersed in 100 mL deionized water with pH = 8.0, and 0.083 g of polyallylamine hydrochloride was added in 50 mL solution, respectively. After 30 min of reaction at 25℃ and 150 rpm, centrifugation was performed at 4000 rpm for 12 min, and water washing was performed for 3 times. Then, 0.083 g of polyacrylic acid was added in 50 mL solution, and after 35 min of reaction at 25℃ and 150 rpm, centrifugation and washing were performed. Then, 0.045 g of amino-modified nanosilica was added in 56 mL dispersion, and after 45 min of reaction at 25℃ and 150 rpm, centrifugation and washing were performed. The above assembly cycle was repeated for 2 times, and vacuum drying was performed at 50℃ for 6 h to obtain the anti-mosquito microcapsules.
[0040] Example 2
[0041] A preparation method of anti-mosquito microcapsules, comprising the following steps:
[0042] Step 1: 1 g of citronella oil, 1.5 g of lemon grass oil, and 3 g of peppermint oil were mixed to obtain a core material; 0.6 g of sodium lignosulfonate and 0.4 g of Tween-80 were dissolved in 100 mL deionized water, and ultrasonic treatment was performed at 300 W for 15 min until dissolution. The pH was adjusted to 8.0 by using 0.1 mol / L NaOH, and the core material was added. Homogenization was performed at 8000 rpm for 5 min, and then ultrasonic treatment was performed at 400 W for 12 min to obtain a core material emulsion.
[0043] Step 2: 1.0 g of nanohydroxyapatite was dispersed in 50 mL of ethanol-water mixture (volume ratio 3:1), and ultrasonic treatment was performed at 500 W for 30 min. The pH was adjusted to 5.5, 0.06 g of aminopropyltriethoxysilane was added, and reaction was performed at 65℃ and 200 rpm under nitrogen protection for 5 h. Centrifugation and drying were performed to obtain silane-modified nanohydroxyapatite. The silane-modified nanohydroxyapatite was dispersed in 50 mL of Tris-HCl buffer with pH = 8.2, 0.043 g of dopamine hydrochloride was added, and reaction was performed at 28℃ and 200 rpm with oxygen flow of 20 mL / min for 10 h. Centrifugation and drying were performed to obtain silane-dopamine complex-modified nanohydroxyapatite.
[0044] Step 3: 106 g of the core material emulsion was taken, 2.5 g of the silane-dopamine complex-modified nanohydroxyapatite was added, and ultrasonic treatment was performed at 300 W for 10 min. 9 g of diisocyanate was slowly added dropwise, and reaction was performed at 30℃ and 250 rpm for 1.5 h. Then, 0.3 g of dopamine hydrochloride was added in 12 mL of aqueous solution, and reaction was continuously performed at 40℃ and 250 rpm with oxygen flow of 20 mL / min for 8 h. Centrifugation was performed at 8000 rpm for 8 min, and water washing was performed for 3 times to obtain nanocomposite microcapsules.
[0045] Step 4: 0.5 g of nano-silica was dispersed in 50 mL of ethanol-water mixture (volume ratio 4:1) by ultrasonic treatment at 400 W for 25 min, and the pH was adjusted to 5.5. Then, 0.06 g of aminopropyltriethoxysilane was added, and the mixture was refluxed at 85°C under nitrogen protection at 180 rpm for 9 h. After centrifugation at 8000 rpm for 12 min, the product was washed with anhydrous ethanol for 3 times and water for 2 times, and then dried at 70°C under vacuum for 5 h to obtain aminated nano-silica.
[0046] Step 5: 1.0 g of nano-composite microcapsules was dispersed in 100 mL of deionized water by ultrasonic treatment at 200 W for 5 min, and then 0.03 g of sodium dodecyl benzene sulfonate was added. The mixture was stirred at 25°C at 150 rpm for 30 min, and then centrifuged at 4000 rpm for 10 min. The product was washed with deionized water for 3 times and dried at 50°C to obtain pretreated microcapsules.
[0047] The pretreated microcapsules were dispersed in 100 mL of deionized water with pH=8.0, and then 0.083 g of polyallylamine hydrochloride was added in 50 mL of solution. The mixture was reacted at 25°C at 150 rpm for 30 min, and then centrifuged at 4000 rpm for 12 min and washed with water for 3 times. Then, 0.083 g of polyacrylic acid was added in 50 mL of solution, and the mixture was reacted at 25°C at 150 rpm for 35 min. Then, 0.045 g of aminated nano-silica was added in 56 mL of dispersion, and the mixture was reacted at 25°C at 150 rpm for 45 min. The above assembly cycle was repeated for 2 times, and the product was dried at 50°C under vacuum for 6 h to obtain mosquito-repellent microcapsules.
[0048] Example 3
[0049] A method for preparing mosquito-repellent microcapsules, comprising the following steps:
[0050] Step 1: 1 g of citronella oil, 2 g of lemon grass oil, and 3.5 g of peppermint oil were mixed to obtain a core material. 0.6 g of sodium lignosulfonate and 0.4 g of Tween-80 were dissolved in 100 mL of deionized water by ultrasonic treatment at 300 W for 15 min, and the pH was adjusted to 8.0 with 0.1 mol / L NaOH. Then, the core material was added, and the mixture was homogenized at 8000 rpm for 5 min and then ultrasonically treated at 400 W for 12 min to obtain a core material emulsion.
[0051] Step 2: 1.0 g of nano-hydroxyapatite was dispersed in 50 mL of ethanol-water mixture (volume ratio 3:1) and ultrasonicated at 500 W for 30 min. The pH was adjusted to 5.5, 0.08 g of aminopropyl triethoxysilane was added, and the reaction was carried out at 65°C under nitrogen protection and stirring at 200 rpm for 5 h. The product was obtained by centrifugation, washing and drying. The product was dispersed in 50 mL of Tris-HCl buffer solution with pH=8.2, 0.043 g of dopamine hydrochloride was added, and the reaction was carried out at 28°C under stirring at 200 rpm and oxygen flow of 20 mL / min for 10 h. The product was obtained by centrifugation, washing and drying.
[0052] Step 3: 106 g of core material emulsion was taken, 3.0 g of silane-dopamine composite modified nano-hydroxyapatite was added, and ultrasonication was carried out at 300 W for 10 min. 10 g of diisocyanate was added dropwise, and the reaction was carried out at 30°C under stirring at 250 rpm for 1.5 h. Then, 0.3 g of dopamine hydrochloride was added in 12 mL of aqueous solution, and the reaction was carried out under oxygen flow (20 mL / min) at 40°C under stirring at 250 rpm for 8 h. The product was obtained by centrifugation at 8000 rpm for 8 min and washing with water for 3 times.
[0053] Step 4: 0.5 g of nano-silicon dioxide was dispersed in 50 mL of ethanol-water mixture (volume ratio 4:1) and ultrasonicated at 400 W for 25 min. The pH was adjusted to 5.5, 0.08 g of aminopropyl triethoxysilane was added, and the reaction was carried out at 85°C under reflux and stirring at 180 rpm for 9 h. The product was obtained by centrifugation at 8000 rpm for 12 min, washing with anhydrous ethanol for 3 times, washing with water for 2 times, and vacuum drying at 70°C for 5 h.
[0054] Step 5: 1.0 g of nano-composite microcapsule was taken, 100 mL of deionized water was added, and ultrasonication was carried out at 200 W for 5 min to disperse. 0.04 g of sodium dodecyl benzene sulfonate was added, and the reaction was carried out at 25°C under stirring at 150 rpm for 30 min. The product was obtained by centrifugation at 4000 rpm for 10 min, washing with deionized water for 3 times, and drying at 50°C.
[0055] The pretreated microcapsule was dispersed in 100 mL of deionized water with pH=8.0, and 0.083 g of polyallylamine hydrochloride was added in 50 mL of solution. The reaction was carried out at 25°C under stirring at 150 rpm for 30 min, followed by centrifugation at 4000 rpm for 12 min and washing with water for 3 times. Then, 0.083 g of polyacrylic acid was added in 50 mL of solution, and the reaction was carried out at 25°C under stirring at 150 rpm for 35 min. The product was obtained by centrifugation and washing. Then, 0.045 g of aminated nano-silicon dioxide was added in 56 mL of dispersion, and the reaction was carried out at 25°C under stirring at 150 rpm for 45 min. The product was obtained by centrifugation and washing. The above assembly cycle was repeated for 2 times, and the product was obtained by vacuum drying at 50°C for 6 h.
[0056] Example 4
[0057] A preparation method of an anti-mosquito microcapsule, comprising the following steps:
[0058] Step 1: 1 g of citronella oil, 3 g of lemongrass oil and 5 g of peppermint oil are mixed to obtain a core material; 0.6 g of sodium lignosulfonate and 0.4 g of Tween-80 are dissolved in 100 mL of deionized water, and ultrasonic treatment is performed at 300 W for 15 min until dissolution; 0.1 mol / L NaOH is used to adjust the pH to 8.0; the core material is added; homogenization is performed at 8000 rpm for 5 min; and then ultrasonic treatment is performed at 400 W for 12 min to obtain a core material emulsion.
[0059] Step 2: 1.0 g of nano-hydroxyapatite is dispersed in 50 mL of an ethanol-water mixture (volume ratio 3:1), ultrasonic treatment is performed at 500 W for 30 min, the pH is adjusted to 5.5, 0.10 g of aminopropyl triethoxysilane is added, and reaction is performed at 65°C under nitrogen protection and stirring at 200 rpm for 5 h; centrifugal washing and drying are performed to obtain silane-modified nano-hydroxyapatite; the silane-modified nano-hydroxyapatite is dispersed in 50 mL of a Tris-HCl buffer solution with a pH of 8.2, 0.043 g of dopamine hydrochloride is added, reaction is performed at 28°C under stirring at 200 rpm and with oxygen gas being passed at a flow rate of 20 mL / min for 10 h, and centrifugal washing and drying are performed to obtain silane-dopamine composite-modified nano-hydroxyapatite.
[0060] Step 3: 106 g of the core material emulsion is taken, 4.24 g of the silane-dopamine composite-modified nano-hydroxyapatite is added, ultrasonic treatment is performed at 300 W for 10 min, 12.72 g of diisocyanate is slowly added dropwise, reaction is performed at 30°C under stirring at 250 rpm for 1.5 h; 12 mL of an aqueous solution containing 0.3 g of dopamine hydrochloride is further added, oxygen gas is passed (20 mL / min), reaction is continuously performed at 40°C under stirring at 250 rpm for 8 h, centrifugal separation is performed at 8000 rpm for 8 min, and water washing is performed three times to obtain nano-composite microcapsules.
[0061] Step 4: 0.5 g of nano-silicon dioxide is dispersed in 50 mL of an ethanol-water mixture (volume ratio 4:1), ultrasonic treatment is performed at 400 W for 25 min, the pH is adjusted to 5.5, 0.10 g of aminopropyl triethoxysilane is added, and reaction is performed at 85°C under reflux and stirring at 180 rpm for 9 h under nitrogen protection; centrifugal separation is performed at 8000 rpm for 12 min, anhydrous ethanol washing is performed three times, water washing is performed twice, and vacuum drying is performed at 70°C for 5 h to obtain aminated nano-silicon dioxide.
[0062] Step 5: 1.0 g of the nano-composite microcapsules is taken, 100 mL of deionized water is added, ultrasonic treatment is performed at 200 W for 5 min until dispersion, 0.06 g of sodium dodecyl benzene sulfonate is added, stirring is performed at 25°C and 150 rpm for 30 min, centrifugal separation is performed at 4000 rpm for 10 min, deionized water washing is performed three times, and drying is performed at 50°C to obtain pretreated microcapsules.
[0063] The pretreated microcapsules were dispersed in 100 mL deionized water with pH = 8.0, and 0.083 g of polyallylamine hydrochloride was added in 50 mL solution, respectively. After 30 min of reaction at 25℃ and 150 rpm, centrifugation was performed at 4000 rpm for 12 min, and water washing was performed for 3 times. Then, 0.083 g of polyacrylic acid was added in 50 mL solution, and after 35 min of reaction at 25℃ and 150 rpm, centrifugation and washing were performed. Then, 0.045 g of amino-modified nanosilica was added in 56 mL dispersion, and after 45 min of reaction at 25℃ and 150 rpm, centrifugation and washing were performed. The above assembly cycle was repeated for 2 times, and vacuum drying was performed at 50℃ for 6 h to obtain the anti-mosquito microcapsules.
[0064] Example 5
[0065] A preparation method of anti-mosquito microcapsules, comprising the following steps:
[0066] Step 1: 1 g of citronella oil, 1 g of lemon grass oil, and 2 g of peppermint oil were mixed to obtain a core material; 0.6 g of sodium lignosulfonate and 0.4 g of Tween-80 were dissolved in 100 mL deionized water, and ultrasonic treatment was performed at 300 W for 15 min until dissolution. The pH was adjusted to 8.0 by using 0.1 mol / L NaOH, and the core material was added. Homogenization was performed at 8000 rpm for 5 min, and then ultrasonic treatment was performed at 400 W for 12 min to obtain a core material emulsion.
[0067] Step 2: 1.0 g of nanohydroxyapatite was dispersed in 50 mL of ethanol-water mixture (volume ratio 3:1), and ultrasonic treatment was performed at 500 W for 30 min. The pH was adjusted to 5.5, 0.05 g of aminopropyltriethoxysilane was added, and reaction was performed at 65℃ and 200 rpm under nitrogen protection for 5 h. Centrifugation and drying were performed to obtain silane-modified nanohydroxyapatite. The silane-modified nanohydroxyapatite was dispersed in 50 mL of Tris-HCl buffer with pH = 8.2, 0.043 g of dopamine hydrochloride was added, and reaction was performed at 28℃ and 200 rpm with oxygen flow of 20 mL / min for 10 h. Centrifugation and drying were performed to obtain silane-dopamine complex-modified nanohydroxyapatite.
[0068] Step 3: 106 g of the core material emulsion was taken, 2.12 g of the silane-dopamine complex-modified nanohydroxyapatite was added, and ultrasonic treatment was performed at 300 W for 10 min. 8.48 g of diisocyanate was slowly added dropwise, and reaction was performed at 30℃ and 250 rpm for 1.5 h. Then, 0.3 g of dopamine hydrochloride was added in 12 mL of aqueous solution, and reaction was continuously performed at 40℃ and 250 rpm with oxygen flow of 20 mL / min for 8 h. Centrifugation was performed at 8000 rpm for 8 min, and water washing was performed for 3 times to obtain nanocomposite microcapsules.
[0069] Step 4: 0.5 g of nano-silica was dispersed in 50 mL of ethanol-water mixture (volume ratio 4:1) by ultrasonic treatment at 400 W for 25 min. The pH was adjusted to 5.5, and 0.05 g of aminopropyltriethoxysilane was added. The mixture was refluxed at 85°C under nitrogen protection at 180 rpm for 9 h. After centrifugation at 8000 rpm for 12 min, the product was washed with anhydrous ethanol for 3 times and water for 2 times, and then dried at 70°C under vacuum for 5 h to obtain aminated nano-silica.
[0070] Step 5: 1.0 g of nano-composite microcapsules was added to 100 mL of deionized water, and dispersed by ultrasonic treatment at 200 W for 5 min. Then, 0.02 g of sodium dodecyl benzene sulfonate was added, and the mixture was stirred at 25°C at 150 rpm for 30 min. After centrifugation at 4000 rpm for 10 min, the product was washed with deionized water for 3 times and dried at 50°C to obtain pretreated microcapsules.
[0071] The pretreated microcapsules were dispersed in 100 mL of deionized water with pH = 8.0. Then, 50 mL of a solution containing 0.083 g of polyallylamine hydrochloride was added, and the mixture was reacted at 25°C at 150 rpm for 30 min. After centrifugation at 4000 rpm for 12 min and washing with water for 3 times, 50 mL of a solution containing 0.083 g of polyacrylic acid was added, and the mixture was reacted at 25°C at 150 rpm for 35 min. After centrifugation and washing, 56 mL of a dispersion containing 0.045 g of aminated nano-silica was added, and the mixture was reacted at 25°C at 150 rpm for 45 min. After centrifugation and washing, the above assembly cycle was repeated for 2 times. Finally, the product was dried at 50°C under vacuum for 6 h to obtain mosquito-repellent microcapsules.
[0072] Comparative Example 1: The difference between Comparative Example 1 and Example 1 is that step 2 is omitted in the preparation process of mosquito-repellent microcapsules, and no silane-dopamine composite modified nano-hydroxyapatite is added in step 3.
[0073] Comparative Example 2: The difference between Comparative Example 2 and Example 1 is that steps 4 and 5 are omitted in the preparation process of mosquito-repellent microcapsules.
[0074] Comparative Example 3: The difference between Comparative Example 3 and Example 1 is that the nano-composite microcapsules are not pretreated in step 5.
[0075] Performance Test:
[0076] 1. Microcapsule shell material compressive strength test: a nano-mechanical testing system is used, equipped with a flat-ended indenter (diameter 5 pm); after drying, the mosquito-repellent microcapsules are uniformly dispersed on a glass slide, and a pressure is applied to a single microcapsule at a loading rate of 0.1 mN / s at room temperature (25°C) until the shell material breaks (an obvious drop point appears in the load-displacement curve), and the maximum pressure value at the time of breakage is recorded; the contact area is calculated according to the microcapsule particle size, and the compressive strength is calculated according to the formula compressive strength = maximum pressure / contact area; 20 complete microcapsules are randomly tested, and the average value (unit: MPa) is taken. The test results are shown in Table 1.
[0077] 2. Anti-breakage test: according to GB / T 3921-2008 "Textiles - Colour fastness tests - Colour fastness to soaping", the mosquito-repellent microcapsules are mixed with a 10wt% polyvinyl alcohol solution at a mass ratio of 1:1 to prepare a working solution, and a 10cm x 10cm cotton fabric (gram weight 180g / m 2 ) is treated by padding (pad pickup 80%) to obtain a test fabric containing microcapsules; the test fabric is placed in a 40°C, 1g / L standard soap solution, washed with a shaking washing machine, each time for 30min, a total of 5 times, and dried at room temperature after washing; the morphology of the microcapsules on the surface of the fabric is observed by optical microscopy, and the proportion of the number of broken microcapsules (microcapsules with obvious cracks in the shell material or leakage of the core material) to the total number of microcapsules is calculated, which is the breakage rate. The test results are shown in Table 1.
[0078] 3. Mosquito repellency rate test: 2g of mosquito-repellent microcapsules are evenly applied to a 5cm x 5cm qualitative filter paper (application area 25cm 2 ), placed in a 20cm x 20cm x 20cm sealed glass box, 50 female Culex pipiens pallens (3-5 days after emergence, without blood sucking) are placed on one side of the glass box, and the test filter paper is placed on the other side, and the mosquito repellency rate within 2h is recorded (mosquito repellency rate = number of mosquitoes not contacting the filter paper / total number of mosquitoes x 100%). The test results are shown in Table 1.
[0079] Table 1:
[0080] Compressive strength of shell material (MPa) Breaking rate (%) Mosquito repellency rate (%) Example 1 18.0 7.2 98.5 Example 2 16.3 8.7 98.3 Example 3 17.5 7.9 98.5 Example 4 18.6 6.5 98.7 Example 5 14.8 9.6 98.2 Comparative Example 1 7.8 35.6 98.4 Comparative Example 2 11.3 28.2 98.6 Comparative Example 3 13.6 19.6 98.3
[0081] Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments, or make equivalent replacements to some of the technical features, any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing mosquito-repellent microcapsules, characterized in that, Includes the following steps: S1. Mix lemongrass oil, lemongrass oil and peppermint oil to obtain core material. Dissolve sodium lignosulfonate and Tween-80 in deionized water, adjust the pH and add it to the core material. After homogenization and ultrasonic treatment, obtain core material emulsion. S2. Disperse nano-hydroxyapatite in a mixed solution of ethanol and water, react it with aminopropyltriethoxysilane to obtain silane-modified nano-hydroxyapatite, and then react it with dopamine hydrochloride in the presence of oxygen to obtain silane-dopamine composite-modified nano-hydroxyapatite. S3. Mix the core material emulsion with silane-dopamine composite modified nano-hydroxyapatite, add diisocyanate to react, then add dopamine aqueous solution and pass oxygen to continue the reaction. After centrifugation and washing, nanocomposite microcapsules are obtained. S4. Disperse nano-silica in a mixed solution of ethanol and water, react it with aminopropyltriethoxysilane, and obtain aminated nano-silica by centrifugation, washing and drying. S5. The nanocomposite microcapsules are sequentially assembled with polyallylamine hydrochloride, polyacrylic acid, and aminated nano-silica in multiple layers, and after repeated cycles, the mosquito repellent microcapsules are obtained after drying.
2. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S1, the mass ratio of lemongrass oil, lemongrass oil, and peppermint oil is 1:1 to 3:2 to 5.
3. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S2, the mass ratio of nano-hydroxyapatite to aminopropyltriethoxysilane is 10:0.5-1.
0.
4. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S3, the amount of silane-dopamine composite modified nano-hydroxyapatite added is 2-4 wt% of the core material emulsion.
5. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S3, the amount of diisocyanate added is 8 to 12 wt% of the core material emulsion.
6. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S4, the mass ratio of nano-silica to aminopropyltriethoxysilane is 10:1 to 2.
7. The method for preparing a mosquito-repellent microcapsule according to claim 1, characterized in that, In step S5, the nanocomposite microcapsules undergo pretreatment, including the following steps: The nanocomposite microcapsules were added to deionized water, ultrasonically dispersed, and then sodium dodecylbenzenesulfonate was added. The mixture was stirred and reacted, and after centrifugation, washing, and drying, pretreated nanocomposite microcapsules were obtained.
8. The method for preparing a mosquito-repellent microcapsule according to claim 7, characterized in that, The amount of sodium dodecylbenzenesulfonate added is 2-6% of the amount of nanocomposite microcapsules.
9. A mosquito-repellent microcapsule, characterized in that, It is prepared by the method described in any one of claims 1-8.
10. The application of the mosquito-repellent microcapsule according to claim 9 in a fabric finishing agent.